The Effects of Exergaming and Neurofeedback on Working Memory in Children with Attention-Deficit/Hyperactivity Disorder - Heydarian , Majid; Daneshfar, Afkham; Shojaei , Masoumeh; Molanorouzi , Keyvan (Psychological Research in Individuals with Exceptional Needs, 2026)
This study aimed to compare the immediate and sustained effects of neurofeedback and exergaming on working memory in children with attention-deficit/hyperactivity disorder. This applied experimental study used a randomized pretest–posttest–follow-up design with four groups. The participants were 52 boys aged 7–10 years with attention-deficit/hyperactivity disorder who attended mainstream primary schools in Qazvin, Iran, during the 2021–2022 academic year. After matching for intelligence and selected demographic characteristics, participants were randomly assigned to neurofeedback, sham neurofeedback, exergaming, and control groups. The neurofeedback and exergaming groups each included 14 participants, whereas the sham neurofeedback and control groups each included 12 participants. The intervention groups completed 30 sessions, conducted three times per week for 45 minutes. Working memory was assessed using the computerized N-Back Task at pretest, posttest, and one-month follow-up. Data were analyzed using a two-factor mixed analysis of variance and bootstrapped Bonferroni-adjusted pairwise comparisons in SPSS version 26. The main effect of time on working memory was significant, F(2, 96) = 53.04, p < .001, partial η² = .52. The main effect of group was also significant, F(3, 48) = 3.66, p = .019, partial η² = .18, and the time-by-group interaction was significant, F(6, 96) = 15.07, p < .001, partial η² = .48. At posttest, neurofeedback produced significantly greater improvement than sham neurofeedback (p = .018) and control (p = .010), while exergaming outperformed control (p = .002). At follow-up, neurofeedback remained superior to sham neurofeedback (p = .001) and control (p = .004), and exergaming remained superior to control (p = .001). No significant differences were found between neurofeedback and exergaming at posttest or follow-up. Both neurofeedback and exergaming were effective in improving working memory in children with attention-deficit/hyperactivity disorder, and their effects were maintained one month after treatment; however, neither intervention demonstrated clear superiority over the other.